Bilateral scapulothoracic osteochondromas in a patient with hereditary multiple exostosis: a case report and review of the literature - Rupp, Markus; Hardes, Jendrik; Raschke, Michael J.; Skwara, Adrian; Justus Liebig University Giessen (My University, 2016)
Hereditary multiple exostosis (HME) is an autosomal dominant disorder characterized by two or more benign growing, cartilage capped tumors of long bones called osteochondromas. If abnormal growth and clinical symptoms of osteochondromas newly appear in adults, malignant transformation of the usually benign growing tumors should be suspected and diagnostic testing should be initiated. Against the background of hypothesized higher malignant transformation of osteochondromas into chondrosarcoma in individuals with shoulder exostoses, we report a case of bilateral scapulothoracic osteochondromas in a patient suffering from HME. A 60-year-old female with HME complained of chest pain while being hospitalized for bilateral femoral fractures. A computed tomography scan of the chest was performed to rule out pulmonary embolism. However, bilateral osteochondromas in the scapulothoracic spaces were detected. Due to absence of radiographic evidences for malignant transformation in the patient, invasive diagnostic procedures such as biopsy and histological examination were recommended in order to exclude malignant transformation of both osteochondromas. Physicians should be aware that patients with HME who present with shoulder pain should be examined for osteochondromas in the scapulothoracic space. Due to possible sarcomatous transformation, regular follow-ups are necessary for adolescents and adults.
Keywords: Osteochondroma; hereditary multiple exostosis; scapulothoracic pain; malignant transformation; mesenchymal tumor; ddc:610